Epistemological Tensions between Qur’anic Revisionism and Decolonial Thought: A New Concept Integrative-Critical Tafsir - Alif Hibatullah; Abdul Kadir Riyadi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This study examines the epistemological tension between devisionism and decolonial thought in contemporary Qur’anic studies. Revisionism emphasizes the historical-critical examination of the Qur’an as a human artifact, while decolonialism highlights the importance of epistemic autonomy grounded in both spiritual authority and rationality. The study employs a qualitative-descriptive approach with a comparative analysis of key scholars such as Patricia Crone, Michael Cook, and Joseph Lumbard, etc. The findings reveal a significant gap in the previous literature, as both paradigms have often been studied separately without efforts toward synthesis. Through theoretical analysis, this article proposes an integrative-critical tafsir model that combines the methodological precision of Western philology with the spiritual and ethical awareness of Islamic epistemology. By restoring Muslim epistemic agency while maintaining academic rigor, this framework provides a transformative middle ground for relevant Islamic scholarship. The case study of surah Al-Baqarah verse 144, concerning the change of the qiblah, is used to demonstrate how historical accuracy can coexist with spiritual meaning. This research affirms that integrative-critical interpretation offers a new epistemological framework for Qur’anic studies one that is both scientifically grounded and spiritually rooted bridging Western rationality and Islamic revelation, while guiding scholars to navigate the intersection of history, revelation, and wisdom through a more epistemically comprehensive interpretive methodology.